Global dynamics of a discrete viral infection model with time delay, virus-to-cell and cell-to-cell transmissions. Issue 11 (2nd November 2017) - Zhou, Jinling; Yang, Yu
Abstract: We present a nonstandard finite difference scheme for a delayed viral infection model with virus-to-cell and cell-to-cell transmissions. We prove that the system is permanent if the basic reproduction numberR 0 > 1 . Then we show that the infection-free equilibrium is globally asymptotically stable ifR 0 ≤ 1, and the infection equilibrium is globally asymptotically stable ifR 0 > 1 . Numerical simulations are presented to illustrate our theoretical results.